Taiwan's democracy on trial : political change during the Chen Shui-bian era and beyond - Copper, John Franklin (Univ Press of America, 2010)
This book assesses the process of democratization in Taiwan during the Chen Shui-bian Era and after. He shows that in several respects, press freedom, human rights, ethnic relations, political reform, constitutionalism, and clean governance, democratization regressed. Economic management was not good and relations with the United States were severely strained.